Profile of people with stomas from a municipal health service in Southern of Brazil (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To characterize the sociodemographic and clinical profile of the population with stoma that resides in the city of Uruguaiana(Rio Grande do Sul, Brazil). Method: A quantitative, documental, retrospective and exploratory study realized in May 2016. It were analyzed 34 forms of people with stomas; descriptive and percentage statistics were applied. Results: Men predominance (55.9%) and a higher incidence in the 61-70 age group (32.3%) were identified. The neoplasias are the main cause for the manufacture of stomas(61.7%), all of which are intestinal (100%). Conclusion: It is believed that this research may contribute to the planning of adequate and specialized assistance for these people. The identification of the Family Health Strategy to which each user belongs will assist in the planning of future actions in order to provide care that offers guidance and support.
Keywords: Stoma; Stomatherapy; Nursing; Health profile